2000
DOI: 10.1073/pnas.97.10.5450
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for a link between complement and the vascular complications of diabetes

Abstract: Activated terminal complement proteins C5b to C9 form the membrane attack complex (MAC) pore. Insertion of the MAC into endothelial cell membranes causes the release of growth factors that stimulate tissue growth and proliferation. The complement regulatory membrane protein CD59 restricts MAC formation. Because increased cell proliferation characterizes the major chronic vascular complications of human diabetes and because increased glucose levels in diabetes cause protein glycation and impairment of protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
159
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(168 citation statements)
references
References 43 publications
8
159
0
1
Order By: Relevance
“…CD59, prevent formation of MACs on the self-tissue. The increased blood glucose in diabetic patients could induce glycation of complement regulatory proteins and by this mean inactivate the proteins [38]. Glycation of CD59 happens in vivo in humans, but not in C57 mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD59, prevent formation of MACs on the self-tissue. The increased blood glucose in diabetic patients could induce glycation of complement regulatory proteins and by this mean inactivate the proteins [38]. Glycation of CD59 happens in vivo in humans, but not in C57 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Glycation of CD59 happens in vivo in humans, but not in C57 mice. This glycation attenuates its capacity to inhibit MAC formation [38]. It has been shown that MAC formation happens on cells and can lead to the release of growth factors without effects on cell viability [39].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in vitro, complement activation and sublytic formation of the terminal complement complex on mammalian cells may induce release of growth factors, leading to vascular alternations (26)(27)(28)(29)(30)(31). In addition, glycation of complement regulatory proteins has been shown to decrease their regulatory capacity and increase complement activation in diabetes (32,33). These mechanisms might contribute to development of late diabetes complications and to the excess mortality in diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, increased concentrations of inflammatory markers, such as CRP and interleukin-6, have been involved in the development and progression of long-term diabetic macrovascular complications [18]. On the other hand, a shortened erythrocyte half-life has been reported in diabetes [19] and the metabolic syndrome has been related to increased RDW levels [20], leading us to postulate a possible influence of an underlying inflammatory state (the occurrence of which is typical in diabetes mellitus and the metabolic syndrome [18]) on accelerated erythrocyte destruction. In the present study, we observed increased CRP levels in the quartiles with highest RDW.…”
Section: Discussionmentioning
confidence: 99%